Romantisme dalam Lirik Lagu "Komang" Karya Raim Laode - Pauline Dewi Juliani Setyaningsih; Adam Yogantara; Anita Tri Tyaswanti; Titik Sudiatmi; Wahyu Dini Septiari (Jurnal Komunitas Bahasa, 2023)
The purpose of this study is to describe the romance in the song â€œKomangâ€ by Raim Laode. This study uses descriptive qualitative methods and love triangle theory to reveal romance in Raim Laode's Komang song. The source of the research data is the lyrics of the song Komang by Raim Laode. Data collection is done by listening to songs and reading song lyrics scripts, then taking notes and data grouped according to aspects of romance. Data analysis techniques use descriptive analysis models interactively. The results of this study show that Komang's song has aspects of romance, namely intimacy, passion, and commitment.